3D and Animated Lenticular Photography : Between Utopia and Entertainment. - Timby, Kim (De Gruyter, 2015)
Viewers have long been fascinated by photographs that animate with a flick of the wrist or appear three-dimensional without the use of special devices. Both are made possible by the lenticular process. Broadly weaving this technology into scientific and popular culture, this volume sheds new light on our relationship to photographic realism and on the forceful interplay in photography between innovation and the desire to be entertained.- Resumé vydavatel
Keywords: fotografie; trojrozměrné zobrazování; zpracování obrazu; rozpoznávání vzorů; photography; three-dimensional imaging; image processing; pattern recognition; elektronické knihy; studie; electronic books; studies